Resonant double phase equations. (April 2022) - Papageorgiou, Nikolaos S.; Rădulescu, Vicenţiu D.; Zhang, Youpei
Abstract: We consider a double phase Dirichlet equation with a reaction which is asymptotically as x → ± ∞, resonant with respect to the first eigenvalue of a related eigenvalue problem. Using variational tools together with Morse theoretic arguments, we prove the existence of at least two bounded nontrivial solutions for the problem.